ÁBDIQÁDIR BEKIMBET ULÍNÍŃ MÁDENIY-AǴARTÍWShÍLÍQ KÓZQARASLARÍ - Seytmuratov, Qalbay (ILIM hám JÁMIYET, 2026)
The state is considering the cultural and educational views of the talented poet Abdukadir Bekimbet oglu, a martyr and enlightened son of the Karakalpak people.